SOSIALISASI UPAYA PENCEGAHAN STUNTING MELALUI PEMANFAATAN PRODUK PETERNAKAN DI DESA WAIHERU KECAMATAN TELUK AMBON - Joris, Lily; Fredriksz, Shirley; Rehatta, Lea M (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is a chronic nutritional problem caused by a prolonged lack of nutrient intake, leading to impaired growth in children. The long-term effects of stunting include decreased cognitive development, weakened immune systems making children more susceptible to illness, an increased risk of metabolic diseases such as obesity, heart disease, and vascular disorders, as well as learning difficulties. The underlying factors of stunting include insufficient calorie and protein intake, socio-economic factors (poverty), improper parenting due to a lack of knowledge and education for pregnant and breastfeeding mothers, and low education and awareness regarding proper feeding practices for infants and toddlers (adequate breastfeeding). To address this issue, counseling and socialization on the role of animal protein in complementary feeding (MPASI) are necessary to provide knowledge and awareness for mothers about stunting prevention by utilizing livestock products such as milk, meat, and eggs. Evaluation results indicate that the counseling and socialization efforts have successfully enhanced participants' understanding and encouraged them to apply the information they received. This initiative is further supported by the local government of Waiheru Village, which is also committed to reducing stunting prevalence, making this effort highly beneficial.